Structural changes in the progression of atrial fibrillation: potential role of glycogen and fibrosis as perpetuating factors - Zhang, Ling (Int J Clin Exp Pathol, 2015)
Background: Previous studies of the goat heart subjected to prolonged atrial pacing induced sustained atrial fibrillation (AF). Structural changes included marked accumulation of glycogen in atrial myocytes. Aims: In the present study, we hypothesized that glycogen deposition in canine atrial myocytes promotes paroxysmal forms of AF and is involved in fibrosis development in the later stages of AF. Material & methods: In dogs under pentobarbital anesthesia, tissues were obtained from the right and left atrial appendages (LAA/RAA). Periodic acid Schiff (PAS) and Masson’s trichrome staining of the LAA/RAA from normal dogs, and those subjected to atrial pacing induced AF for 48 h or 8 weeks determined glycogen and collagen concentrations, respectively, using morphometric analysis. Results: At baseline, there was a significant greater concentration of glycogen in the LAA than the RAA (P ≤ 0.05). Compared to the RAA, the LAA glycogen, was dense and locked against the intercalated discs. After pacing induced AF for 48 hours and 8 weeks there was a marked increase in glycogen deposition, significantly greater than in the baseline state (P ≤ 0.05). There was a similar and progressive increase in collagen concentrations in each group (P ≤ 0.05). Conclusions: The differential in glycogen concentration, in conjunction with other factors, neural and electrophysiological, provide a basis for the greater propensity of the left atrium for paroxysmal AF, at baseline and 48 hours of pacing induced AF. The marked increase in collagen at 8 weeks of pacing provides a substrate for sustained AF. Evidence is presented linking glycogen accumulation and fibrosis as factors in the persistent forms of AF.